Complementary therapies for pregnancy and childbirth (Baillière Tindall, 2000)
(Bailliere Tindall) Univ. of Greenwich, UK. Text covering history and background of complementary and alternative approaches to health care in pregnancy and childbirth. Discusses current research and applications, and includes new chapters on chiropractic, hypnotherapy, Bach Flower remedies, and Alexander Technique. Previous edition: c1995. Softcover